2019
DOI: 10.17138/tgft(7)200-209
|View full text |Cite
|
Sign up to set email alerts
|

Leucaena for paper industry in Gujarat, India: Case study

Abstract: Keynote paper presented at the International Leucaena Conference, 1‒3 November 2018, Brisbane, Queensland, Australia.India is one of the major producers/consumers of paper and pulp products (3–4% of global share). Approximately one-fourth of industry raw material has come from wood-based plantations from the 1990s onwards. The greatest development challenge faced by the industry since that time is sourcing robust raw material from agroforestry on private lands. Following genetic improvement of leucaena (Leucae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Proximate and Amino Acid Analysis of L. leucocephala Mature Pods Leucaena leucocephala, also known as petai belalang in Malaysia, is one of the fast-growing leguminous trees (Sethi and Kulkarni 1995). In India, it is an important plant that is encouraged to be grown under social forestry schemes, as it provides useful timber and paper industry (Khanna et al 2019). In this study, the proximate and amino acid composition of L. leucocephala mature pods were investigated, and its suitability for the raw material for isolation of nanocrystalline cellulose was determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximate and Amino Acid Analysis of L. leucocephala Mature Pods Leucaena leucocephala, also known as petai belalang in Malaysia, is one of the fast-growing leguminous trees (Sethi and Kulkarni 1995). In India, it is an important plant that is encouraged to be grown under social forestry schemes, as it provides useful timber and paper industry (Khanna et al 2019). In this study, the proximate and amino acid composition of L. leucocephala mature pods were investigated, and its suitability for the raw material for isolation of nanocrystalline cellulose was determined.…”
Section: Resultsmentioning
confidence: 99%
“…The species is also used for pulp and paper production due to its low lignin content (Pandey and Kumar 2013). In India, a Leucaena leucocephala farm forestry plantation program initiated by JK Paper Ltd had been developed because of its potential to be used as a new material for the paper industry (Khanna et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The JK Paper Ltd company in Gujarat, India, in their program to produce higher-yielding clones for paper pulp, uses misting chambers to produce rooted cuttings of their best clonal selections of L. leucocephala and of a triploid hybrid of L. leucocephala × L. collinsii (Khanna et al 2019). Nulik and Kana Hau (2019) reported success with bare-stem seedlings generated in purpose-sown highdensity nurseries or by retrieval of volunteer seedlings under established tree rows.…”
Section: Establishment and Management Of Leucaenamentioning
confidence: 99%
“…Tarramba, as well as many hybrid lines, showed excellent potential as biofuel and recommended planting configurations that provided triple bottom-line benefits. Khanna et al (2019) reported that India was a major producer and consumer of paper and pulp products and has developed leucaena plantations to provide raw materials for industry. One of the largest Indian paper companies (JK Paper Ltd) has promoted establishment of leucaena plantations in Gujarat, Maharashtra and Madhya Pradesh States with >7,800 farmers planting areas totalling >18,400 ha for producing paper pulp.…”
Section: Alternative Uses Of Leucaenamentioning
confidence: 99%
“…The wood is strong and medium density, and suitable for carpentry materials. Its caloric value as fuelwood is about 4600 calories per kg, and its biochar improves soil property of crop fields [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%